Male Writers of DānměiLiterature: An Analysis of Fēitiānyèxiáng - Wang, Aiqing (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2021)
In  this  paper,  I  investigate dānměias  a  ground-breaking  literary  genre by  means  of  scrutinising  an  illustrious  male  writer  pseudonymed Fēitiānyèxiáng, and I propound that his works are exemplary as online writing.  As  a  growing  Chinese  Internet  literature,  the  female-oriented dānměigenre, aka  Boys  Love,  has  attracted  legions  of  heterosexual fangirl  producers  and  consumers  as  well  as  a  meagre  amount  of  their male counterparts. Among male dānměiwriters, who are in an absolute minority, Fēitiānyèxiángis  celebrated  fora  wide  range  of  innovative themes  and  magnificent  storylines,  and  his  fiction  is  replete  with profound literary and historical allusionsand elaborate and meticulous depictions.  Furthermore,  notwithstanding  a non-reversible  bipartite dichotomy between seme (top) and uke (bottom)roles, Fēitiānyèxiáng’s writing  is  not  featured  by  feminisation  of  uke,  which  is  clichéd characterisation in not only the dānměi subculture, but also classical and modern    Chinese    literature.    More    significantly, Fēitiānyèxiáng’s narratives  are  reality-oriented,  addressing adverse  circumstances  in  a real-world  context  and  hence  rendering  characters  more  multi-faceted, and he does not circumvent realistic issues or create over-romanticised representation, analogous to his equivalent pseudonymed Nánkāngbáiqǐ.